Evaluation of the Effect of Tightening Torque on Single-lap Bolted Joints - Boualamallah, D.; Ghazi, A.; Miloudi, A.; Merzoug, M. (Engineering, Technology & Applied Science Research, 2022)
In this experimental research, a set of tests was conducted on single-lap bolted joints in terms of choosing between two types of bolts and exploiting the optimal solution for connecting samples. Then the effect of the tightening torque on the mechanical behavior of single-lap joints was evaluated. Six simple tensile tests were performed with different values of torque and the results are reported.